Implementation of the payments for environmental services program for biodiversity conservation in the soil and water conservation district of Caquetá, Belén de los Andaquíes - Borda, Carlos (2024)
Infographic with general data on the Works for Taxes project, which promotes biodiversity conservation, climate change mitigation and peace building in Colombia. The project includes a payment for environmental services scheme that would benefit ASPROABELÉN, an association of cocoa producers in the Colombian department of Caquetá.